2019
DOI: 10.1021/acs.jpca.8b12262
|View full text |Cite
|
Sign up to set email alerts
|

Magic Numbers for the Photoelectron Anisotropy in Li-Doped Dimethyl Ether Clusters

Abstract: Photoelectron velocity map imaging of Li(CH 3 OCH 3 ) n clusters (1 ≤ n ≤ 175) is used to search for magic numbers related to the photoelectron anisotropy. Comparison with density functional calculations reveals magic numbers at n = 4, 5, and 6, resulting from the symmetric charge distribution with high s-character of the highest occupied molecular orbital. Since each of these three cluster si… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 58 publications
(155 reference statements)
0
4
0
Order By: Relevance
“…[2][3][4][5] In bulk solutions the paramagnetic species have been investigated via electron spin resonance (ESR) 6 and nuclear magnetic resonance (NMR) spectroscopy 7 (and references therein). Neutral sodium doped ammonia clusters Na(NH 3 ) n have previously served as model systems to study the electronic properties of the 'ammoniated' electron via photoion spectroscopy, photoelectron spectroscopy and ab initio methods [8][9][10][11][12][13][14][15][16][17][18][19][20] (and references therein). Photoion spectroscopy has revealed that the ion appearance energy of Na(NH 3 ) n decreases systematically with increasing number of solvent molecules 15 (and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] In bulk solutions the paramagnetic species have been investigated via electron spin resonance (ESR) 6 and nuclear magnetic resonance (NMR) spectroscopy 7 (and references therein). Neutral sodium doped ammonia clusters Na(NH 3 ) n have previously served as model systems to study the electronic properties of the 'ammoniated' electron via photoion spectroscopy, photoelectron spectroscopy and ab initio methods [8][9][10][11][12][13][14][15][16][17][18][19][20] (and references therein). Photoion spectroscopy has revealed that the ion appearance energy of Na(NH 3 ) n decreases systematically with increasing number of solvent molecules 15 (and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…Along the metal identity axis, thorium makes the most exotic species forming a Th­(NH 3 ) 10 complex with four diffuse peripheral electrons (article in preparation). Moving along the second axis of the chemical space (ligand identity), water, dimethyl ether, , crown ethers, methanol, , cyclams, cryptands, methylated ammonia, , and diamines have been shown to create similar systems with various coordination numbers, stabilities, and reactivity.…”
Section: Introductionmentioning
confidence: 99%
“…These are commonly composed of alkali, alkaline earth, aluminum, oxygen and nitrogen atoms, 6 or even metallic clusters. 14 Expanded metals are similar to organic electrides 15 but the ligands are solvent molecules known to solvate electrons, such as ammonia, 5 water, [16][17][18][19][20] dimethyl ether, 21,22 methanol, 23,24 methylamine, [25][26][27][28][29][30][31] acetonitrile, 32 hexamethylphosphoric triamide (HMPA) 33,34 and tetra-hydrofuran. 35 Electrides and expanded metals can be unified under the general category of solvent separated electrons from metals ions.…”
Section: Introductionmentioning
confidence: 99%